Pemalsuan Identitas Dalam Praktik Poligami Ilegal - Daulay, R. Fahmi Natigor (Faculty of Law, University of Mataram, 2025)
Polygamy is a marriage practice that is strictly regulated under Indonesian law, requiring court permission and consent from the first wife. However, some men circumvent legal procedures by committing identity fraud, such as using false names or concealing their previous marital status. This research analyzes the legal consequences of identity fraud in unauthorized polygamy and the marriage annulment process. The research method uses normative juridical approach with descriptive secondary data. The results show that identity fraud causes the dissolution of marital bonds with annulment processes following divorce proceedings procedures, and judicial considerations that are legally binding from both positive law and fiqh perspectives. Keywords: Identity Fraud, Illegal Polygamy, Marriage Annulment.